Phase 1 study of DS‐1205c combined with gefitinib for EGFR mutation‐positive non‐small cell lung cancer - Koichi Goto; Yoshimasa Shiraishi; Haruyasu Murakami; Hidehito Horinouchi; Ryo Toyozawa; Masayuki Takeda; Makiko Uno; Nigel Crawford; Joseph McGill; Takeshi Jimbo; Masato Ishigami; Gensuke Takayama; et al. (Cancer Medicine, 2023)
Abstract Background Tyrosine kinase inhibitors (TKIs) are effective for the treatment of non‐small cell lung cancer (NSCLC) patients with activating mutations of the epidermal growth factor receptor (EGFR), but responses are not durable as tumors develop resistance. DS‐1205c is a novel, specific, orally bioavailable, small‐molecule AXL receptor TKI. In preclinical studies, DS‐1205c restored TKI antitumor activity in a TKI acquired‐resistance EGFR‐mutant NSCLC tumor xenograft model. Methods This first‐in‐human, multicenter, open‐label Phase 1 study (registered at ClinicalTrials.gov: NCT03599518) primarily evaluated the safety and tolerability of combination therapy with DS‐1205c and gefitinib in Japanese patients with metastatic or unresectable EGFR‐mutant NSCLC and tumor progression during treatment with EGFR‐TKIs. Patients (n = 20) received DS‐1205c monotherapy (200–1200 mg twice daily [BID]) in a 7‐day safety monitoring period before combination DS‐1205c/gefitinib (250 mg once daily) in 21‐day cycles. Results The observed common treatment‐emergent adverse events (TEAEs) were increased aspartate aminotransferase (35%), increased alanine aminotransferase (30%), rash maculo‐papular (30%), and diarrhea (25%). No serious TEAEs were reported. Plasma concentrations and pharmacokinetic parameters of DS‐1205a (free form of DS‐1205c) were unaffected by concomitant administration of gefitinib. No patient achieved a complete or partial response and 5 patients (25%) had stable disease. Conclusion DS‐1205c was generally safe and well tolerated at all dose levels, but the safety profile of ≤800 mg BID was more favorable than 1200 mg BID. The recommended dose for dose‐expansion cohorts of DS‐1205c in combination therapy with gefitinib was 800 mg BID.